AN OVERVIEW ON ELOPEMENT MAR RIAGE OF RONGMEI TRIBES - Rajkumari, Mary Sana; Rajkumari, Mary Sana (International Journal of Psychosocial Rehabilitation, 2020)
Human marriage is the root for the origin of family and the procreation as well as for the growth of society. Since the ancient time male and female wants to live together in peace. In ancient time before the establishment and regulating the marriage system man and women who live in distant places recognize themselves and fall in love each other and started to live together as husband and wife. Of course hatred among the clan or between the same clan caused unprecedented tensions creates serious problems in the society or in the village. To eradi cate this social hazard wise man and thinkers of the pre historic period framed the laws of Rongmei marriage. The unwanted confrontation within the village and the other villages had been somehow controlled and chaos created by elopement gradually reduced because of stringent punishment and regulation.Thus the practice of arranged marriage established in society. The nature and habits of love of human being and needs of early as sociation had transformed to auspicious solemnization. Since the thousand year of civilization the act of indo mitable love and human emotion caused the root of elopement within restriction from the pre historic period. The practice of love and elopement marriage continued and that provokes different emotional reaction and creates much violence in the society. In the present generation this abominable habits has been abolished through the negotiation. Many oral narratives and memoirs depicted such social adjustment in the past and present of the Rongmei Society.